ANALYSIS OF THE BANK'S INTERNAL OPERATIONAL SYSTEM AT BANK SYARIAH INDONESIA (BSI) UNISMA FUNDING OFFICE - Daidan, Muhammad Rafli; Fauziah, Annisa Putri; Kurniati, Rini Rahayu (PERCIPIENCE International Journal of Social, Administration, & Entrepreneurship, 2025)
This study aims to obtain a general overview of the operational system of Bank Syariah Indonesia at KF Malang Unisma. The researcher used the method of collecting primary data obtained through observation and internal interviews with employees of Bank Syariah KF Malang Unisma. In determining informants, the method used is the purposive sampling method, namely by sampling data sources with certain considerations and in accordance with the problem to be researched. To analyze the validity of the data that has been collected, the researcher uses a confirmability test by reflecting the researcher's findings in a journal or desiminiting the findings at a conference to get input in the findings. It is proven that judging from several aspects of Bank Syariah Indonesia KF Malang UNISMA runs the bank's operational system quite well. In terms of functions, BSI plays the role of investment managers, investors, carries out social functions, and financial service providers very well and uses sharia principles in accordance with the provisions of the National Sharia Council and the Indonesian Ulema Council.